Tolerance of Ruppia sinensis Seeds to Desiccation, Low Temperature, and High Salinity With Special Reference to Long-Term Seed Storage - Gu, Ruiting; Zhou, Yi; Song, Xiaoyue; Xu, Shaochun; Zhang, Xiaomei; Lin, Haiying; Xu, Shuai; Yue, Shidong; Zhu, Shuyu (Frontiers in Plant Science, 2018)
Seeds are important materials for the restoration of globally-threatened marine angiosperm (seagrass) populations. In this study, we investigated the differences between different Ruppia sinensis seed types and developed two feasible long-term R. sinensis seed storage methods. The ability of R. sinensis seeds to tolerate the short-term desiccation and extreme cold had been investigated. The tolerance of R. sinensis seeds to long- term exposure of high salinity, cold temperature, and desiccation had been considered as potential methods for long-term seed storage. Also, three morphological and nine physiological indices were measured and compared between two types of seeds: Shape L and Shape S. We found that: 1) Wet storage at a salinity of 30-40 psu and 0℃ were the optimal long-term storage conditions, and the proportion of viable seeds reached over 90% after a storage period of 11 months since the seeds were collected from the reproductive shoots; 2) dry condition was not the optimal choice for long-term storage of R. sinensis seeds; however, storing seeds in a dry condition at 5℃ and 33+10% relative humidity for 9 months had a relatively high percentage (74.44 + 2.22%) of viable seeds, consequently desiccation exposure could also be an acceptable seed storage method; 3) R. sinensis seeds would lose vigor in the interaction of extreme cold (-27℃) and desiccation; 4) there were significant differences in seed weight, seed curvature, and endocarp thickness between the two types of seeds; These findings provided basic seed-related ecological information for R. sinensis and support the long-term storage of its seeds. Our results may also serve as useful information for seagrass seed storage and restoration programs.